New insights into intermediate-temperature solid oxide fuel cells with oxygen-ion conducting electrolyte act as a catalyst for NO decomposition - Bu, Yun-Fei; Ding, Dong; Gan, Lu; Xiong, Xun-Hui; Cai, Wei; Tan, Wen-Yi; Zhong, Qin (Applied catalysis. B, Environmental, 2014)
Nitrogen oxides (NOx) can cause many environmental problems, such as acid rain, smog, and ozone depletion. So many methods are used for removing it. At present, more and more reports are focused on NOx decomposition, Ceramic membrane, electrochemical deNOx and SOFC. In addition Perovskites oxides have been extensively investigated as suitable materials for them. Direct decomposition of NO requires high temperature. The influence of oxygen and carbon dioxide are obstacles for the remove of NO for the ceramic membrane reactor. For SOFC, the reported paper is less, and the focus is on the traditional cathode materials, which has good performance on the reduction of oxygen, but to NO activity generally is not high. So we use perovskite materials as a point of intersection to those different ways. It not only requires high activity for NO decomposition, but also can be used as the SOFC electrodes. The feasibility is confirmed through a series of characterization, which brings new insights into solid oxide fuel cells with oxygen-ion conducting electrolyte act as a catalyst for NO decomposition. •LBMM–SDC as a catalyst for NO decomposition is evaluated as a cathode for SOFCs.•The electrical performance the cell was improved with the addition of oxygen.•The electrochemical system based on IT-SOFC can be used for NO decomposition under 600°C. The environmental problems and supply of clean and economical energy is grand global challenges. Direct decomposition of nitrogen oxides (NOx) is the most ideal and effective approach for NOx removal by catalysis, which has the great potential to alleviate the air pollution. On the other hand, solid oxide fuel cells (SOFCs) are one of the cleanest, most efficient chemical-to-electrical energy conversion systems. Here we reported a new electrochemical system to combine the traditional catalyst for direct decomposition of NOx with an electric generation process through a SOFC. By nano-sized La0.4Ba0.6Mn0.8Mg0.2O3–δ (LBMM), an effective catalyst widely used for NOx decomposition, adopting an anode-support SOFC configuration, which consisted with the conventional NiO-samarium doped ceria (SDC) anode, and thin film SDC electrolyte, we demonstrated that complete decomposition of NOx and a peak power density of 25mWcm−2 at 600°C when Ar containing 5% NO and 5% O2 was fed to the cathode and 10% H2 was used the fuel. The effect of the ratio between NO and O2 was found to be critical for the NO conversion and SOFC performance. The dependence of temperature and gas composition on NO conversion was also investigated.